Biomarkers of Potential Harm: Summary of an FDA-Sponsored Public Workshop. Issue 1 (14th December 2017) - Chang, Cindy M; Cheng, Yu-Ching; Cho, Taehyeon M; Mishina, Elena V; Del Valle-Pinero, Arseima Y; van Bemmel, Dana M; Hatsukami, Dorothy K
Abstract: Introduction: Since 2009, the United States (US) Food and Drug Administration (FDA) Center for Tobacco Products (CTP) has had the authority to regulate the manufacture, distribution, and marketing of tobacco products in order to reduce the death and disease caused by tobacco use. Biomarkers could play an important role across a number of FDA regulatory activities, including assessing new and modified risk tobacco products and identifying and evaluating potential product standards. Methods: On April 4–5, 2016, FDA/CTP hosted a public workshop focused on biomarkers of potential harm (BOPH) with participants from government, industry, academia, and other organizations. The workshop was divided into five sessions focused on: (1) overview of BOPH; (2) cardiovascular disease (CVD); (3) chronic obstructive pulmonary disease (COPD); (4) cancer; and (5) new areas of research. Results and Conclusions: The deliberations from the workshop noted some promising BOPH but also highlighted the lack of systematic effort to identify BOPH that would have utility and validity for evaluating tobacco products. Research areas that could further strengthen the applicability of BOPH to tobacco regulatory science include the exploration of composite biomarkers as predictors of disease risk, "omics" biomarkers, and examining biomarkers using existing cohorts, surveys, and experimental studies. Implications: This paper synthesizes the main findings from the 2016 FDA-sponsored workshop focused on BOPH and highlights research areas that could further strengthen the science around BOPH and their applicability to tobacco regulatory science.